Lessons from the COVID-19 pandemic: a national survey of gender-based violence services at Canada’s post-secondary institutions - Wright, JJ (Jessica); Abji, Salina (My University, 2022)
The COVID-19 pandemic was described as an “unprecedented time” for post-secondary institutions (PSIs) across Canada. Campus closures, the pivot to virtual classrooms, and new health and safety measures have left a significant mark on campus life. While the impacts of COVID-19 on learning and research were often the focus of campus measures, less attention has been paid to how the pandemic affected the work to address and prevent sexual and gender-based violence (GBV) at PSIs. Yet we know that GBV is a global problem that has been categorized as a “shadow” pandemic by the UN, and that PSIs have a significant role to play in GBV prevention education, response, and policy/research leadership on this issue. To help bring more attention to the impacts of COVID-19 on GBV education and response efforts at PSIs, the Courage to Act project initiated a national survey of GBV frontline workers and others involved in GBV efforts at PSIs. Courage to Act is a national initiative focused on addressing and preventing GBV at PSIs in Canada. Leveraging our network of 3500 stakeholders and over 170 of Canada’s top GBV experts and advocates, Courage to Act conducted two surveys, one in 2021 and 2022. Both surveys invited participants to comment on the impacts of COVID-19, as well as innovations and priorities for addressing and preventing GBV at PSIs moving forward. A total of 104 participants responded, mostly frontline GBV workers on campus, but also administrators and students involved in this work. While the results of this community-based research study were not representative of all campus communities, there were important themes that emerged in our analysis. We extrapolated from these themes to identify six major “lessons from the pandemic” for PSIs to consider. These lessons provide insight into how the movement to end campus GBV can build back the momentum for preventing and addressing GBV that was lost due to COVID-19.
Keywords: gender-based violence; post-secondary institutions; COVID-19 pandemic